Face-off: defacement, ethics and the 'neighbour' in The Comedy of Errors. Issue 8 (14th September 2018) - Ashby, Richard
ABSTRACT: Recent accounts of The Comedy of Errors have concentrated on the profound loss of self that takes place in the play – a loss that not only compromises social roles, but also imperils the imagined physical integrity of the body. This threat to the body in The Comedy of Errors manifests itself most compellingly in the fear of being defaced, of having the face wiped away, overlaid with wrinkles or rent apart by others. Drawing on the work of Jacques Lacan and Slavoj Žižek, I contend that defacement is a recurrent preoccupation of The Comedy of Errors, a play that dramatises how a lack of inter-subjective recognition causes the individual features that constitute the face to mutate into blank 'defeatures'. By concentrating on the way in which a lack of recognition results in defacement, I draw particular attention to the ethical challenge posed by the play: how to accommodate and respond to the Neighbour, the other that, by failing to reflect the self, challenges the identity of the subject.